Pemanfaatan Media Pembelajaran Berbasis Quizizz dalam Meningkatkan Kemampuan Mufradat Siswa Kelas XI di MA Muhammadiyah Kota Bima - Alamsyah Alamsyah; Muslimin Muslimin; Nurdiniawati Nurdiniawati; Agus Salam (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Vocabulary mastery is an important aspect of Arabic language learning because it serves as the foundation for students to understand and use the language effectively. However, in practice many students still experience difficulties in mastering vocabulary due to the lack of engaging and interactive learning media. This study aims to improve students’ vocabulary mastery through the use of Quizizz-based learning media. This research employed Classroom Action Research (CAR) conducted in two cycles consisting of planning, action, observation, and reflection. The subjects of this study were 12 students of class XI at MA Muhammadiyah Kota Bima. Data were collected through observation, tests, and documentation, and analyzed using descriptive quantitative analysis by calculating the average score and the percentage of students’ learning mastery. The results show that the use of Quizizz learning media can improve students’ vocabulary mastery. The students’ average score increased from 67 in the pre-cycle to 75.17 in cycle I and 80.67 in cycle II. The percentage of learning mastery also increased from 16.7% in the pre-cycle to 50% in cycle I and 83.33% in cycle II. Therefore, Quizizz-based learning media proved to be effective in improving students’ Arabic vocabulary mastery.